An exploration of the editing cut as an articulator in film through frequency domain analysis of spectator EEGs - Sanz-Aznar, Javier (Frontiers in Neuroscience, 2025)
IntroductionThis study explores if the cinematographic cut can be considered an articulation axis between different units, which are adjacent shots. The theoretical premise of the research was that if the shot change functions as a point of articulation that produces a connection between different units, two conditions must be met: first, all types of editing cuts should elicit common neural patterns; and second, these neural patterns triggered to make sense of the shot change should exhibit variations depending on the specific type of cut.MethodsTo achieve this objective, building on the theoretical foundations of cinematographic language and integrating methodologies from cognitive neuroscience, the study analyzed neural responses triggered by continuity editing cuts through electroencephalography recordings from 21 participants.ResultsTo determine it, the frequency domain of spectators’ neural recordings were analyzed for common event-related desynchronization/synchronization patterns. The analysis revealed neural responses patterns in theta synchronization and delta desynchronization, which are associated with memory encoding, narrative segmentation, and meaning construction.DiscussionMoreover, the results suggests that shot changes are cognitively processed as relational events, not merely as new perceptual inputs. These findings support the hypothesis that the shot change by cut is neurally processed as an articulatory mechanism within film structure.